Analysis of Translation Techniques and Syntactic in Translation of the Kediri State Islamic Institute for the Academic Community of the Arabic Education Study Program - Afyuddin, Moh. Sholeh; Gunawan, Riski (Institut Agama Islam Negeri (IAIN) Kediri, 2021)
The name does not have the connotation of a particular language meaning, except to indicate what it is named after. Thus the name does not need to be translated into another language. In fact, when translated it will be prone to misunderstandings about what is meant. In the case of the translation of IAIN Kediri into Arabic carried out by the academic community of the Arabic language education study program, more than one variety of translations emerged, namely: 1) الجامعة الإسلامية الحكومية كديري dan 2) جامعة كديريالإسلامية الحكومية . This is due to differences in the techniques used to translate them. This inconsistency certainly resulted in the emergence of the allegation that the campus in question was different. This study uses a qualitative method by taking data from several student writings contained in thesis documents, papers, journal articles and books published by IAIN Kediri, web pages, and others and trying to find the most popular variety of translations. The findings of the analysis conclude that the technique of determining the equivalent of words in the two translations is exactly the same, namely using the generalization technique on the word institute, the reduction technique in the translation of Islamic religious words, the literal technique on the word Negeri and the borrowing technique which is naturalized on the word Kediri. Syntactic analysis concludes that there is a grammatical gap in the first translation model due to the use of a literal method that is oriented to the source text. While in the second translation model there is no grammatical gap, because the translation uses transmutation techniques so that the translation results have a pattern that is known in the target language.